The role of entrepreneurial imaginativeness for implementation intentions in new venture creation - Michael Asenkerschbaumer; Andrea Greven; Malte Brettel (International Entrepreneurship and Management Journal, 2023)
Implementation intentions, as conceptualized in the Rubicon model of action phases, facilitate the initiation of intended action. As a self-regulatory strategy, implementation intentions avoid the shortcoming of intention models (i.e., theory of planned behavior), which are able only partially to explain the variance of action caused by entrepreneurial intention. While early studies have shown the efficacy of implementation intentions in complex settings such as entrepreneurship (inter alia), an understanding of how implementation intentions come into play is missing. We address this gap and build on a unique sample of 161 responses from entrepreneurs receiving a grant for venture creation between 2018 and 2022 to investigate the role of entrepreneurial imaginativeness in implementation intentions. We find support for a curvilinear relationship between creative and practical imaginativeness and implementation intentions. Our study contributes theoretically to all frameworks that guide it, theory of implementation intentions and the Rubicon model and mindset theory of action phases, and validates them in the entrepreneurial context. By establishing entrepreneurial imaginativeness as an antecedent of implementation intentions, we provide entrepreneurs with a recipe for implementation intentions and add to the extant research on consequents of entrepreneurial imaginativeness.
Keywords: L26; M13; 650; Entrepreneurial imaginativeness; Implementation intentions; Rubicon model of action phases; New venture creation